(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The logistics sector is pivotal in ensuring seamless supply chain operations, and with the global transition toward digitalization, digital logistics has emerged as a transformative force in enhancing operational efficiency and competitiveness. This paper explores the opportunities for developing digital logistics in Uzbekistan, a country strategically located at the crossroads of Europe and Asia. The study identifies the potential benefits of integrating advanced digital tools such as blockchain, IoT, and AI into logistics operations, highlighting their impact on cost reduction, transparency, and supply chain optimization. It also examines Uzbekistan’s current logistics infrastructure, government policies, and digital transformation initiatives, addressing challenges such as limited technological infrastructure and workforce readiness. By benchmarking against successful case studies from other regions, the study provides actionable recommendations to foster the growth of digital logistics in Uzbekistan.